Free radical and nitric oxide scavenging activities of cynometra cauliflora leaves extract - Noor Mohamed, Nurul Tartila (2017)
The aim of this study was to evaluate on the free radical and nitric oxide scavenging activity of Cynometra cauliflora leaves. C. cauliflora is one of the plants that has been underutilized but is believed to have many beneficial effects on health. In this study, the antioxidants and nitric oxide scavenging activity of C. cauliflora leaves were studied using the 2,2-diphenyl-l-picrylhydrazil (DPPH) and nitric oxide scavenging assay. DPPH which is a stable free radical, is used to measure the antioxidant potentials of C. cauliflora in scavenging the free radicals. Nitric oxide scavenging assay was also developed to generate nitric oxide and evaluate the scavenging activity by C. cauliflora. From the results, the IC50 value of C. cauliflora was 21.94 µg/ml and was compared to the standard antioxidant; quercetin with ICso of 2.253µgml. Quercetin was a better antioxidant as it is required at a lower concentration to scavenge the DPPH free radicals. The IC so of both control and extract for the nitric oxide scavenging assay was not obtained. Quercetin and C. cauliflora scavenged 22% and 15% NO respectively, at 200µg. The results suggested that C. cauliflora leaves have potential in antioxidant activities and could be beneficial for developing compounds which is natural and non-toxic. Further studies should be conducted to explore the potential and benefits of C. cauliflora in other activities as well as its potential to counteract diseases associated with oxidative stress.